HOW THE LOCAL GOVERNMENT PROMOTE THEIR TOURISM DESTINATION TOWARD ADVERTISEMENT: A CASE STUDY OF TRANSLATION - Edwar Kemal; Sri Imelwaty; Muthia Damaiyanti (Cirebon International Conference on Education and Economics Proceeding, 2024)
After covid 19, Indonesia as one of the affected country tries to raise their economic sectors. One of the ways to improve the economic growth is from the tourism sectors. The local governments of Indonesian country try to promote their tourism destination by using online and offline advertisement. On the advertisements, they write the information by using English and Indonesian language. This research was to analyze how the local government promotes their tourism destination towards advertisement. It used a qualitative research by using case study design. Data were collected from a brochure written by the local government containing the tourism destination information and it used a document checklist for the research instrument. Then, data were analyzed by using the content analysis and theory from Larson about translation. The research shows that most of the translations are in the types of literal translation where it makes the information is unclear. Then, it is also found that there are some lexical equivalences having incorrect diction and ambiguity meaning in the target language for translating some of cultural materials. By conducting this research, it is expected that the local government could improve the way they inform their tourism destination well because it will give clear and accurate information for the tourist.